A bibliometrics study of phase change materials (PCMs) - Qin, Yinghong; Ghalambaz, Mohammad; Sheremet, Mikhail A.; Fteiti, Mehdi A.; Alresheedi, Faisal (Journal of energy storage)
Articles on phase change materials (PCMs) were subjected to a scientometric study to determine the leading organizations, nations, journals, and topic areas over the last four decades. According to the analysis, there were significantly more publications on PCM between 2011 and 2022. In terms of total publications and total citations, China, the US, and India were discovered to be the top three nations. The country with the most citations per article was Singapore. Considering the collaboration aspect, the research revealed that Saudi Arabia exhibited the most extensive level of international collaboration. Chinese Acad Sci, Xi An Jiao Tong Univ, Univ Lleida, South China Univ Technol, and Sichuan Univ ranked first through fifth in terms of total publications. The most scientific work was produced in the Energy & Fuels topic area of PCM, while China was more active in the Web of Science topic areas. The rise in PCM publications in recent years is indicative of the field's expanding significance and interest in energy storage and sustainable energy. The importance of a multidisciplinary approach to the subject of PCM is highlighted by the high level of cooperation among nations and institutions. Examining keyword trends from 1991 to 2022 shows a growth in the use of “Thermal conductivity” beginning in 1999, a steady mention of “Latent Heat Storage” after 2010, and a consistent usage of “Energy storage” since 2005.